Morphological characterization of cassava roots for equipment design - ., Nabilatou; Philemon , Doua; Bitjoka, Laurent; Njintang, Nicolas; Victor Epane, Mondo (International Journal of Engineering and Technology, 2024)
Cassava (Manihot esculenta, Crantz), native from Latin America, is one of the main food crops which contribute to ensure alimentary security in Cameroon. In Adamawa region, especially in NGAN’HA area, it is one of the principal food crops cultivated, but not really exploited. According to FAO, there are more than 40% of cassava production lost because of lack of processing equipment like conservation and transformation equipment. The purpose of this study is to carry out the morphological characterization of cassava roots to guide cassava processing equipment design. Twenty cassava roots were harvested at NGAN’HA, have been labeled, measured and weighed. The ends of each cassava root were removed, measured and weighed. The different shapes of the remaining part have been identified by analyzing the diameter variations on the root, separated by scission and the dimensions of each piece have been measured according to the 3D basic solids existing shape at which it was closer. The study revealed that for an entire root, we have 240mm to 845mm of length and 0.42 K to 2.54Kg of weight. The analysis of the central part pieces revealed that a major part of roots has cylindrical shapes (68.57%), and followed by truncated conical (22.86%) and spherical (8.57%). The mean value of diameter for cylindrical roots is 72.44mm, 55.3mm and 75.96mm for truncated conical roots respectively for the smallest and the highest diameters. Spherical roots have 71.78mm of mean diameter. The distribution of length and weight or a single root showed that the cylindrical part can represent until 87.50% of the length and 91.89% of the weight; truncated conical part can represent 53.67% of the length and 4% 0f the mass; spherical part can represent 30% of the length and 45% of the mass; the analysis of the ends revealed that they can represent 4.5% of the total mass of roots. Their mean length is 49.39mm for the left ends and 29.11 for the right ends; the mean weights have the same value of 0.03Kg. The characteristics obtained from this study revealed that the model of equipment to design for industrial transformation of cassava is Lathe.